Children as co-researchers. Epistemological, methodological and ethical challenges - Gottfried Schweiger (Cogent Social Sciences, 2024)
This paper explores the involvement of children as co-researchers, tackling core issues in epistemology, methodology, and ethics. It represents a shift in childhood studies, moving away from adult-centered views to recognize children as active agents with valuable insights into their own lives. By conducting a detailed literature review and theoretical analysis, the study highlights the importance of participatory methods that adapt to children’s developmental levels, enabling them to meaningfully contribute across various stages of research, from data collection to analysis and tool selection. This approach underscores the necessity of child-friendly research designs, emphasizing child agency and methodological flexibility. Ultimately, the study finds that engaging children as co-researchers enhances the quality and authenticity of research on childhood. However, achieving this requires addressing power dynamics, ensuring ethical integrity, and tailoring methodologies to respect children’s autonomy. The paper recommends establishing standardized ethical guidelines centered on child participation and suggests participatory frameworks that foster genuine involvement, ensuring research is both rigorous and respectful of children’s unique perspectives.IMPACT STATEMENTThis paper emphasizes the transformative impact of involving children as co-researchers, fundamentally reshaping how childhood studies approach the perspectives and experiences of young participants. By integrating children as active contributors, the study enhances the authenticity, relevance, and ethical integrity of research, offering a model that respects children’s agency and developmental needs. The findings encourage a re-evaluation of research practices, advocating for child-centered ethical guidelines and participatory frameworks that prioritize children’s autonomy and well-being. This approach not only improves research quality but also aligns with broader movements toward inclusivity and empowerment in social sciences, promoting a more equitable, respectful, and impactful understanding of childhood.